Professional Development of Civil Servants of Russia: Legal and Organizational Aspects - PROKOFIEV, Stanislav E.; BOGATYREV, Evgeniy D.; BELYAEV, Alexander M.; EREMIN, Sergey G.; BARMENKOVA, Natalia A. (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018DO - 10.14505//jarle.v9.1(31).28, 2018)
The goal of this article is the study of legal and organizational aspects for professional development of civil servants of Russia and searching for possible ways of improving the existing mechanism of planning, organization and implementation of professional development of civil servants. Methodological basis of the study of the problem of steel General scientific methods such as induction, deduction, analysis, synthesis, grouping, etc. Conducted interdisciplinary analysis of literature and sources on the subject of professional is mand professional development, particularly in relation to public servants. Identified relevant legal issues hindering the process of professional development of civil servants in the context of further education. The proposed solution according to the decision of legal issues, professional development of civil servants. Particular emphasizes placed on finding ways of improving the existing mechanism of planning, organization and implementation of professional development of civil servants at the local level. A proposal about the organization of educational space with in the institutions of various levels of subordination. The leading trend in the development of the principle of professional development of state personnel policies is the requirement for continuous enhancement of the professionalism of the work force through continuous professional development of civil servants, the development of competencies is replaced by installing the development of professional competences and improvement of professional competence. Despite the high level of scientific elaboration of the Institute of professional development of civil servants, as well as the recommendations of the legislator in this direction, the development of modern professionalism of the civil servant becomes the task of the civil servant and the institution where he serves. The study showed that at the present stage, a considerable part of the problema rises in the system of additional professional education of state civil servants, which are by law mandatory. Basically, it is the problems of organizational and legal nature, and their solution requires not just changes at the state and municipal levels, and the drastic reorganization of the existing system of training of civil servants. The beginning of the process can be laid at the local level. In addition to the ʼglobalʼ recommendations for improving the system of professional development of civil servants, a proposal to organize their own educational space with in the institutions of various levels of subordination. The training center will allow not only to optimize the entire mechanism of civil servants' training process and management, but also increase their motivational level for self-development, and the main activities that can increase the efficiency and effectiveness of operations in general